Systematic Understanding of the Mechanisms of Flos Chrysanthemi Indici-mediated Effects on Hypertension via Computational Target Fishing - Chen, Ye-Hui; Lei, Shan-Shan; Li, Bo; Luo, Rong; He, Xinglishang; Wang, Yu-Zhi; Zhou, Fu-Chen; Lv, Gui-Yuan; Chen, Su-Hong (Combinatorial Chemistry & High Throughput Screening, 2020)
Aims and Objective: Hypertension-induced stroke and coronary artery disease are significant causes of global morbidity and mortality. Metabolic hypertension has recently become the leading cause of hypertension. Flos Chrysanthemi Indici (CIF) has a long history as a treatment of hypertension as part of traditional Chinese medicine. However, its mechanisms of activity remain largely unknown. This study was aimed to uncover the potential anti-hypertensive mechanisms of CIF based on network pharmacology. Materials and Methods: In this research, a systems pharmacology approach integrating the measurement of active compounds, target fishing, gene screening, Gene Ontology (GO) pathway analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) Orthology Based Annotation System (KOBAS) database analysis, and compound-target network construction were performed to explore the anti-hypertensive mechanisms of CIF. Results: These studies revealed that 12 bioactive compounds in CIF had good druggability, 5 of which were flavonoids. After screening, 8 of those 12 bioactive compounds interacted with 118 hypertensionrelated target genes, which were mapped to 218 signal pathways. Network analysis showed that these targets were associated with improving insulin resistance, improving vascular function, inhibiting renninangiotensin- aldosterone system (RAAS), inhibiting the sympathetic nervous system (SNS) and regulating other physiological processes. Conclusion: In summary, CIF is predicted to target multiple proteins and pathways to form a network that exerts systematic pharmacological effects in order to regulate blood pressure and metabolic disorder.
Keywords: Flos Chrysanthemi Indici